Outpatient treatment with AZD7442 (tixagevimab/cilgavimab) prevented Covid-19 hospitalizations over 6 months and reduced symptom progression in the TACKLE randomized trial - Hobbs, FDR; Montgomery, H; Padilla, F; Simón-Campos, JA; Kim, K; Arbetter, D; Padilla, KW; Reddy, VP; Seegobin, S; Streicher, K; Templeton, A; Viani, RM; et al. (Springer, 2023)
Introduction We assessed effects of AZD7442 (tixagevimab/cilgavimab) on deaths from any cause or hospitalizations due to coronavirus disease 2019 (COVID-19) and symptom severity and longer-term safety in the TACKLE adult outpatient treatment study.